Adherence and Occurrence of Fractures after Switching to Once-Monthly Oral Bisphophonates - Briesacher, Becky A. (2010)
PURPOSE: Reducing dosing demands of medications generally increases adherence, although this relationship has not been demonstrated with the once-monthly oral bisphosphonates (BP). The study aim is to test whether switching from once-weekly BPs to once-monthly BPs improves adherence and fracture risk. METHODS: This is an interrupted times-series analysis of new users of once-weekly BPs in a nationwide administrative health database from 2003–2007. Participants include 1835 individuals who switched to once-monthly BPs and two propensity-matched comparator groups: 1835 individuals who switched to a different once-weekly BP, and 1835 who did not switch. We measured changes in adequate adherence pre- and post-switch as monthly medication possession ratio >0.80, and calculated incidence rate ratios [IRR] of osteoporotic fractures. RESULTS: All study groups experienced major adherence failure in the first year of therapy: the proportion of adequate adherers was 42% among once-monthly switchers, 47% among once-weekly switchers, and 37% among nonswitchers. However, the once-monthly switch was associated with less adherence failure (4% fewer adherers per month pre-switch vs. 1% fewer adherers per month post-switch, p<.000). There was no statistically significant change in adherence rates for the other groups. We did not detect significantly reduced fracture risk with once-monthly switch: 1 year post-switch, the fracture incidence risk ratios for once-monthly switchers relative to once-weekly switchers were IRR 0.83, 95% CI: 0.50–1.36, and IRR 0.90, 95% CI: 0.54–1.49, relative to nonswitchers). CONCLUSIONS: Reducing the dosing demands of oral bisphosphonates from once-weekly to once-monthly decreased adherence failure but had an uncertain impact on fracture risk.